The Emergence of Rumah Tahfiz: Qur’anic Education and the Muslim Identity Formation in Surakarta - Nur Rohman; Agus Wedi; Elvi Na'imah; Khairul Imam (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2024)
This study aims to discuss the Rumah Tahfiz Qur’an (RTQ), which has recently emerged in several regions of Indonesia. In the historical context of Qur’anic education in Indonesia, these institutions are relatively new. Traditionally, Qur’anic education has been intensively practiced in Islamic boarding schools (pesantren) with their longstanding traditions. However, over the past decade, RTQs have proliferated in various regions. Based on field research in six districts of Solo Raya and drawing on discourse analysis, this article demonstrates that the emergence of RTQs is driven by diverse individuals and social groups, each finding their own responses and followers. Notably, most of the founders and managers are young individuals who lack Qur’anic experience from pesantren or specialized Qur’anic training. Additionally, parents who enroll their children in RTQs generally desire for their children to become proficient in reading and memorizing the Qur’an, while they themselves are occupied with work. This article contributes to the study of contemporary Islamic education by showing how RTQs represent a new trend in Qur’anic learning beyond the traditional pesantren model. It argues that this phenomenon reflects a form of identity seeking among Muslims who strive to remain pious and relevant in contemporary times.